The Linguistic Landscape of Commemorative Plaques and Inscriptions around the Historic Building of the University of Salamanca: Didactic Application for Teaching Spanish as a Foreign Language (Tabanque. Revista Pedagógica, 2025)
This study analyzes the linguistic landscape surrounding the historic building of the University of Salamanca, focusing on the commemorative plaques and inscriptions present in its environment. It shows how these elements, in addition to recalling significant figures or events, function as urban texts that convey values, legitimize narratives, and keep certain collective memories alive. The research proposes using the analysis of these plaques as a teaching resource in Spanish as a foreign language, as they provide students with an authentic context to deepen cultural understanding, develop intercultural awareness, and enhance communicative skills through direct engagement with real linguistic manifestations.
Keywords: linguistic landscape; conmemorative plaques; University of Salamanca; teaching Spanish as a Foreign Language; Spanish didactics